2021
DOI: 10.1111/nep.13959
|View full text |Cite
|
Sign up to set email alerts
|

Oral/oesophageal candidiasis is a risk factor for severe infection after kidney transplantation

Abstract: Aim Bacterial and fungal infections are serious, life‐threatening conditions after kidney transplantation. The development of oral/oesophageal candidiasis after kidney transplantation is not a reported risk factor for subsequent severe infection. This study was performed to investigate the relationship between oral/oesophageal candidiasis after kidney transplantation and the development of subsequent infection requiring hospitalization. Methods This retrospective study included 522 consecutive patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…46 Moreover, oral candidiasis has been observed in 7-52% of patients with neoplastic pathology, who were undergoing chemotherapy and/or radiotherapy in South India and Finland. 47 Recent studies also showed that oral candidiasis was the most common lesion in chronic hepatic failure patients, 48 and a risk factor for severe infection in 36% of patients after kidney transplantation 49 and increased chemoradiotherapy-induced dysphagia in 37% of head-andneck cancer patients. 50…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…46 Moreover, oral candidiasis has been observed in 7-52% of patients with neoplastic pathology, who were undergoing chemotherapy and/or radiotherapy in South India and Finland. 47 Recent studies also showed that oral candidiasis was the most common lesion in chronic hepatic failure patients, 48 and a risk factor for severe infection in 36% of patients after kidney transplantation 49 and increased chemoradiotherapy-induced dysphagia in 37% of head-andneck cancer patients. 50…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%